The history of the Danube as an international waterway from the Roman times until the middle of the 20th century - Zoltán, Huszár (Civilia, 2012)
The study offers a short outline of the 2000 years long history of the most European river, the Danube from the Roman times until the middle of the 20th century. The fact, that the Danube strategy may become an important factor of economic modernization in the EU, and not only in the Middle-European region, but also in Europe as a whole, makes the topic really current. The author's essay can be an interesting addition to it, as it highlights important historical events and economical facts.
Keywords: Danube; international rivers; navigation; the Hapsburg Empire; International Danube Commission